Enhanced Quantum Teleportation between Noninertial Moved Parties by Weak Measurements. Issue 5 (19th February 2019) - Jin, Yao
Abstract: Quantum decoherence caused by the interaction between the quantum system and the environment is the most limiting factor for the applications of quantum teleportation. In this paper, investigated are the dynamic behavior of the coherence of the entangled source and the fidelity of the teleportation for two non‐inertial moved parties suffering the quantum noise induced by the background quantum fields, and a general protection scheme using weak measurements is provided. Explicitly, comparing the cases of using the initial state | Φ ± ⟩ = 1 2 ( | g 1 g 2 ⟩ ± | e 1 e 2 ⟩ ) as well as the initial state | Ψ ± ⟩ = 1 2 ( | e 1 g 2 ⟩ ± | g 1 e 2 ⟩ ), the coherence of the entangled state and teleportation fidelity with and without probabilistic weak measurements are studied. The results show that the decoherence caused by the thermalization of the two parties induced by their non‐inertial movements can be eliminated. The coherence and fidelity can be totally recovered with proper weak measurements and the optimal weak values are shown in relation with the spontaneous emission and excitation rates of the systems. However, the successful probability in the case of using the initial state | Ψ ± ⟩ is found to be much larger than that in the case of using the state | Φ ± ⟩ and the preweak measurement is not needed with the initial state | Ψ ± ⟩ . Abstract : Quantum teleportation for two non‐inertial moved parties is investigated. It is found that the decoherence caused by the thermalization of the two parties induced by their non‐inertial movements can be eliminated. Coherence and fidelity can be totally recovered with proper weak measurements and the optimal weak values are shown in relation with the transition rates of the systems.